Bullying and victimization in children with special educational needs: implications for inclusive practices - Didaskalou, Eleni (2009)
Bullying has been recognized as a widespread, persistent and serious problem occurring in schools across different national contexts. Despite the surge of interest in bullying in recent years, much of the research has focused on its multiple facets and characteristics among non-disabled students, while little is known about its incidence and dimensions in the population of students receiving special education support provision. It is well-known that schooling has generally been constructed and operates around the notions of normalization and homogeneity and children’s diversity often generates discriminating responses contributing to exclusionary educational experiences. In the light of above, the present study aims at exploring the extent and different types of bullying and victimization among Greek students receiving special education support provision. The sample of the study consisted of 173 students attending 5th and 6th primary school grades and participating in pull-out special education delivery programs operating within mainstream schools. According to the findings, participants were actively involved in both bullying and victimization with higher rates in victimization. Bullying was mainly related to physical aggressiveness, humiliating and racist behaviors towards others and social isolation from peers, while victimization included destruction of personal belongings attacked. Statistically significant differences were identified between girls and boys over the different types of bullying and victimization getting involved in, with girls experiencing mostly social isolation and manipulation from others and boys displaying aggressiveness towards others and attacking peers. Statistically significant differences were also found in physical bullying between children receiving more than 12 hours a week special education support and the rest. Children with developmental disabilities tended to use more indirect methods of bullying such as social exclusion more often than children with learning difficulties and children with learning difficulties combined with socio-emotional behavioral disorders. Overall bullying behavior was found to be predicted by presence of playmates during playtime and victimization by absence of playmates during break and limited number of friends in class. The implications of the study for developing school-based inclusive responses to students with SENs, are also discussed. - O bullying tem sido reconhecido como um problema generalizado, persistente e grave que ocorre nas escolas em diferentes contextos nacionais. Apesar da onda de interesse nos comportamentos de bullying ao longo dos últimos anos, grande parte da pesquisa concentrou-se nas suas múltiplas facetas e características entre os estudantes sem deficiência, pouco se sabendo sobre a incidência e dimensões no seio da população estudantil com necessidades educativas especiais. É sabido que a escolaridade tem sido geralmente orientada e opera em função das noções de normalização e de homogeneidade, sendo que a diversidade das crianças gera, muitas vezes, atitudes discriminatórias que contribuem para experiências de exclusão educativa. À luz do exposto, o presente estudo tem por objectivo explorar a extensão e diferentes tipos de bullying e vitimização entre estudantes gregos que recebem apoio ao nível da educação especial. A amostra do estudo foi constituída por 173 alunos do 5 º e 6 º anos do ensino básico que participam em programas de educação especial em funcionamento no seio de escolas regulares. De acordo com os resultados obtidos, verificou-se que os alunos da amostra se encontravam activamente envolvidos em comportamentos de bullying e vitimização, com índices de envolvimento mais elevados de vitimização. O bullying encontrou-se fundamentalmente relacionado aos comportamentos agressivos físicos, comportamentos racistas e de humilhação para com os outros e isolamento social dos seus pares, enquanto a vitimização incluiu a destruição de pertences pessoais e ser atacado. Diferenças estatisticamente significativas foram identificadas entre raparigas e rapazes relativamente aos diferentes tipos de comportamentos de bullying e vitimização em que se envolveram, sendo que as raparigas vivenciaram maioritariamente o isolamento social e a manipulação de outros, e os rapazes exibindo maioritariamente comportamentos de agressividade para com os outros e ataques aos colegas. Diferenças estatisticamente significativas foram também encontradas relativamente aos comportamentos de bullying entre crianças que recebem mais de 12 horas semanais de apoio no ensino especial. Crianças com deficiências de desenvolvimento tendem a usar métodos mais indirectos de bullying, como a exclusão social, mais frequentemente do que crianças com dificuldades de aprendizagem e do que as crianças com dificuldades de aprendizagem combinadas com distúrbios sócio-emocionais e comportamentais. No geral confirmou-se, como factor preditor da ocorrência de comportamentos de bullying, a presença dos colegas durante o recreio, e como factor preditor da vitimização a falta de companheiros durante o intervalo e o número limitado de amigos na sala de aula. As implicações do estudo para o desenvolvimento de respostas baseadas na escola inclusiva para alunos com necessidades educativas especiais, também são discutidas.